Application of Information and Communication Technologies (ICT) to optimize the request for information (RFI) process in construction projects - Sandoval, Ivan Segundo Maza (2023)
Due to the fierce competition that businesses in this industry are engaging in to win difficult projects and improve their projection capabilities, construction projects are currently expanding significantly and adjusting to ongoing changes. Improvements in the management of construction processes are therefore encouraged to speed up project completion, save costs, and boost quality by the projects' baseline or scope. On the other hand, research reveals that common issues that arise during the execution stage include, among others, a lack of information, a lack of a foundational definition, and communication disruptions between departments. Most often, this results in the development of several Requests for Information, which hinders the beneficial flow of operations. Additionally, according to the standard procedure for these requests, a lengthy waiting period is necessary before receiving a response, which entails delays of up to 10%. A new communication method is suggested with the following presumption to speed up project RFI responses. Information and communication technologies (ICT), a crucial resource in the modern world, are used to accomplish this. By centralizing and arranging the information for cross-stakeholder evaluation, these technologies enhance the interchange of project information. By combining technological tools, the proposal redesigns the traditional procedure, which has significantly improved the projects appraised.